PATTERNS OF SEX RA-HO IN THE OIL-SARDINE, SARDINELLA LONGICEPS VAL., AT CALICUT - Raja, B T Antony (Indian Journal of Fisheries, 2011)
Categorising the fish according to maturity, montti of capture and length groups,the data on the sex distribution of the Indian oil-sardine (5flrrfwW/fl/ong'/fepj) collectedat Calicut during 1959-60 to 1965-66 seasons are subjected to statistical tests to find outthenature and cause of dominance of either sex, if any.For the immature fish the overall inference is that there may not be any significantdifierences in the annual recruited population. In the adult fish the possibility ofmore males in May is suggested as due to the fact that the males may start maturing alittle earlier than the females. The dominance of males in 140-150 mm group and that offemales in 170-190 mm groups is brought about by differential growth, the femalesgrowing faster during June to October period. It is recommended that the size of eachsample for sex ratio studies should be at least 50. Based on the earlier and the presentstudies of this author, It is indicated that 375 million ova can be expected from a tonne ofadult biomass of the oil-sardine population.